Mechano-chemical changes of nano sized α-Al2O3 during wet dispersion in stirred ball mills - Peukert, Wolfgang; Stenger, Frank; Götzinger, Martin; Jakob, Peter (Particle & Particle Systems Characterization, 2004)
The mechano-chemical changes in synthetic α-AlO during wet dispersion in a stirred ball mill, are studied. It is shown that a second phase is generated which can be identified as an aluminum hydroxide (Bayerite) by use of dynamic scanning calorimetry (DSC), X-ray diffraction (XRD), thermogravimetry (TG), Fourier transformed infrared (FTIR) spectroscopy and transmission electron microscopy (TEM). The amount of the Bayerite phase produced increases with milling time. A comparison of the evaluated amounts from TG- and DSC-measurements are in reasonable agreement. Furthermore, the measured BET surface area shows a strong dependence on the temperature of sample preparation. Depending on the temperature, the bayerite phase is seen to convert to the α-phase again and also forms meso- and possibly micro-pores, leading to a high BET surface area. In this paper, we highlight the necessity for using different methods to characterize the dispersion process, and for a correct interpretation of the measurement results.
Keywords: α-alumina; Bayerite; Mechano-chemical characterization; Wet dispersing